Off-label combination of leadless pacemakers and subcutaneous defibrillators in bilateral venous occlusion: a new reimplantation strategy after lead extraction. (25th November 2020) - Di Cori, A; Viani, S; Tolve, S; Zucchelli, G; Barletta, V; Giannotti Santoro, M; Parollo, M; Cellamaro, T; Branchitta, G; Carluccio, M; Segreti, L; Paperini, L; et al.
Abstract: Background: Subcutaneous implantable cardioverter-defibrillator (S-ICD) and leadless pacemakers (LPM) provide an alternative to transvenous implantable devices. Sometimes, after transvenous (TV) lead extraction, patients show a bilateral venous occlusion, resulting not eligible for TV reimplantation. Purpose: This analysis was designed to provide preliminary data on feasibility and short-term outcome of an hybrid combination (Hyb) of s-ICD plus LPM after TV-ICD explantation, in patients without anatomical transvenous reimplantation options. Methods: Among 2684 consecutive extracted patients, 31 (1.1%) were reimplanted with a LPM, 66 (2.4%) with a s-ICD and 6 (0.2%) patients with an Hyb combination. Hyb strategy was considered in patients with a pacing plus defibrillating indication, and an anatomical barrier, as bilateral superior venous occlusion or massive bilateral skin erosion. Results: Hyb patients were old (72±10 years), with a prevalent ischemic disease (4/6) and a reduced ejection fraction (43±16%). Extraction indication was infection in 4 and severe venous occlusion in 2, and included 2 single chamber, 2 dual chamber and 2 biventricular ICD. After extraction, reimplantation timing was 7±6 days, LPM was implanted before and sICD the day after. LPM reimplantation indication was sinus node dysfunction in 2 and AV block in 4. Implantation duration was 68±23 and fluoroscopy time 9.4±2.3 min. ICD reimplantation indication was primary prevention in 4 and secondary prevention in 2. Implantation duration was 118±10 min. No complications were observed. At 1 year, no complications were observed, including device related cross-talks. Conclusions: The Hyb strategy is a potential option after TV-ICD explantation in pacemaker dependent patients, when transvenous implantation is not available. Funding Acknowledgement: Type of funding source: None